Optimization of Drying Methods on the Physical and Sensory Stability of Goat Milk Based Kefir Mask Powder - Wahyuningtyas, Amalina Nur; Monasdir, Monasdir; Ismanto, Arif Ismanto; Nurmasytha, Andi; Maulidina, Agil; Yulianti, Karenina Dwi; Izzati, Farah Diba; Muharram, Fadhil (Faculty of Animal Science Universitas Brawijaya, 2026)
Kefir is a fermented milk product rich in bioactive compounds, including lactic acid, antioxidants, and lipids, making it a promising ingredient for facial masks due to its prolonged skin contact and enhanced delivery of active compounds. However, fresh kefir is highly perishable because of its high moisture content and ongoing microbial activity, limiting its storage stability and commercial application. This study aimed to evaluate the effect of two drying methods oven and spray drying on the quality of kefir mask powder derived from goat milk. Key parameters analyzed included moisture content, water activity (aw), fat content, pH, total titratable acidity, total plate count (TPC), yeast count, and sensory acceptance (color, texture, aroma, viscosity, and overall preference). The results showed that the type of drying significantly influenced moisture, aw, and fat levels, while no significant effect was observed on pH, acidity, TPC, or yeast count. Oven drying was more effective in retaining active compounds, whereas spray drying produced a powder with superior sensory characteristics preferred by panelists. These findings suggest that the choice of drying technique should be guided by the desired balance between product stability and consumer appeal.